Contrasting cloud composition between coupled and decoupled marine boundary layer clouds. Issue 19 (1st October 2016) - Wang, Zhen; Mora Ramirez, Marco; Dadashazar, Hossein; MacDonald, Alex B.; Crosbie, Ewan; Bates, Kelvin H.; Coggon, Matthew M.; Craven, Jill S.; Lynch, Peng; Campbell, James R.; Azadi Aghdam, Mojtaba; Woods, Roy K.; et al.
Abstract: Marine stratocumulus clouds often become decoupled from the vertical layer immediately above the ocean surface. This study contrasts cloud chemical composition between coupled and decoupled marine stratocumulus clouds for dissolved nonwater substances. Cloud water and droplet residual particle composition were measured in clouds off the California coast during three airborne experiments in July–August of separate years (Eastern Pacific Emitted Aerosol Cloud Experiment 2011, Nucleation in California Experiment 2013, and Biological and Oceanic Atmospheric Study 2015). Decoupled clouds exhibited significantly lower air‐equivalent mass concentrations in both cloud water and droplet residual particles, consistent with reduced cloud droplet number concentration and subcloud aerosol ( Dp  > 100 nm) number concentration, owing to detachment from surface sources. Nonrefractory submicrometer aerosol measurements show that coupled clouds exhibit higher sulfate mass fractions in droplet residual particles, owing to more abundant precursor emissions from the ocean and ships. Consequently, decoupled clouds exhibited higher mass fractions of organics, nitrate, and ammonium in droplet residual particles, owing to effects of long‐range transport from more distant sources. Sodium and chloride dominated in terms of air‐equivalent concentration in cloud water for coupled clouds, and their mass fractions and concentrations exceeded those in decoupled clouds. Conversely, with the exception of sea‐salt constituents (e.g., Cl, Na, Mg, and K), cloud water mass fractions of all species examined were higher in decoupled clouds relative to coupled clouds. Satellite and Navy Aerosol Analysis and Prediction System‐based reanalysis data are compared with each other, and the airborne data to conclude that limitations in resolving boundary layer processes in a global model prevent it from accurately quantifying observed differences between coupled and decoupled cloud composition. Key Points: Decoupled clouds exhibit lower subcloud aerosol and cloud drop concentrations and more impacted by land sources Coupled clouds have higher total air‐equivalent levels of dissolved nonwater species, with sea salt being dominant Nonwater species mass fractions vary significantly between coupled and decoupled clouds in cloud water and droplet residual particles